INTERNALISASI KETAATAN RELIGIUS SEBAGAI LEGITIMASI KEKUASAAN: STUDI KASUS AMBRUKNYA PONDOK PESANTREN AL KHOZINY SIDOARJO - Achmad Nauval Wildan; Agus Machfud Fauzi (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study examines the relationship between religious obedience and power within religious institutions, focusing on the collapse of the Al Khoziny Islamic boarding school in Sidoarjo. The objective of this research is to analyze how the internalization of religious obedience functions as a form of power legitimation for religious authorities and its implications for social relations and institutional governance within pesantren. This study employs a qualitative approach using a sociological case study method. Data were collected through observation, in-depth interviews, and document analysis, and were analyzed descriptively and qualitatively using Max Weber’s theory of power legitimacy and Pierre Bourdieu’s concept of symbolic domination. The findings indicate that the strong internalization of religious obedience reinforces the charismatic authority of the kiai and produces hierarchical and asymmetrical social relations between leaders and santri. When religious obedience is not accompanied by critical awareness, transparency, and accountability, such legitimacy may obscure structural and ethical weaknesses in institutional management, ultimately leading to a crisis of trust and institutional disintegration. This study emphasizes the importance of balancing religious obedience with social control to prevent religious values from becoming instruments of power domination.